Penanganan Anak ISIS dalam Perspektif Hukum Indonesia - Mohamad Rapik; Bunga Permatasari (Fakultas Hukum Universitas Jambi, 2020)
The involvement of children in the ISIS network has left a complex problem in the legal discourse in Indonesia, including how to deal with children involved in this terrorism network. This article aims to expose the problem of children in conflict with the law in the crime of terrorism. Due to this problem, the Indonesian government is often faced a dilemma between the neccessity to apply serious efforts to eradicate terrorism and the obligation to guarantee a protection to the children. Through a juridical-normative approach, focusing on ISIS children, this article demonstrates that one of the problems in dealing with children involved in terrorism networks lies in the vagueness of the rules addressing the children involved in this terrorism network as well as its implementation by the government. Therefore, this article argues that in order to be able to deal with children involved in terrorism networks, some of the legal instruments concerning the issue, especially the law on terrorism and the laws of children in conflict with the law as long as terrorism is concerned needs to be revised just to accommodate this issue in a more obvious normsto actually maintain a balance between the responsibility to protect the children and the need to preserve stability of the nation and state. Under the new revised laws, the government is hoped to work with and apply the provisions regarding children in conflict with the law in the case of terrorism crimes in the frame of justice and protection for children. Abstrak Keterlibatan anak dalam jaringan ISIS menyisakan permasalahan yang kompleks dalam wacana hukum di Indonesia berikut penanganan anak yang terlibat dalam jaringan terorisme ini. Artikel ini bertujuan untuk memaparkan masalah penangangan anak yang berkonflik dengan hukum dalam tindak pidana terorisme. Terkait hal ini, pemerintah Indonesia seringkali dihadapkan pada dilema antara upaya serius untuk memberantas tindak pidana terorisme dan kewajiban untuk memberikan perlindungan kepada anak. Melalui pendekatan yuridis-normatif, dengan mengambil kasus anak-anak ISIS, artikel ini memperlihatkan bahwa salah satu masalah yang ditemui dalam penanganan anak yang terlibat dalam jaringan terorisme terletak pada ketidakjelasan aturan sejauh menyangkut masalah penangangan anak tersebut berikut pelaksanaannya di lapangan oleh negara. Oleh karena itu, artikel ini berargumen bahwa untuk bisa menangani anak-anak yang terlibat dalam jaringan terorisme, beberapa instrumen hukum yang mengatur masalah ini, utamanya undang-undang terorisme dan undang-undang yang berhubungan dengan anak yang berkonflik dengan hukum harus direvisi guna mengakomodasi permasalahan ini secara lebih jelas yang benar-benar menjaga keseimbangan antara kepentingan anak dan kepentingan bangsa dan negara. Selanjutnya, pemerintah sejatinya mampu mengacu dan menerapkan segala ketentuan hukum yang berlaku mengenai anak yang berkonflik dengan hukum dalam kasus tindak pidana terorisme sebagaimana yang diakomodasi dalam undang-undang tersebut.